PENGARUH AUDIT TENURE, ROTASI AUDITOR, REPUTASI AUDITOR, DAN SPESIALISASI AUDITOR TERHADAP KUALITAS AUDIT - Ade Irma, Fitria; Rispantyo, Rispantyo; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The research aims to know empirical evidence as for factors influencing audit quality of food and beverage firm listed on the Indonesia Stock Exchange. The factors wich analysised in this recearch are audit tenure, auditor rotation, auditor reputation and auditor specialization.The sample of this research is 13 food and beverage firms listed in Indonesia Stock Exchange period 2013-2017 that selected by using purposive sampling method. Technique of analysis for examining the hipotesis was logistic regresion at level significance 5%.The result of this research identify that audit tenure positive significant effect audit quality, where as auditor rotation, auditor reputation and auditor specialization not have anaffect to audit quality of the food and beverage firm listed on the Indonesia Stock Exchange.